Upaya Guru SDN 012 Labuhan Tangga Kecil Terhadap Perencanaan Kurikulum Merdeka Belajar - Oktaviani viani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This research aims to describe teacher readiness and the factors that influence teacher readiness in planning the independent learning curriculum at SDN 012 Labuhan Tangga Kecil. This type of research is descriptive qualitative research. The data sources in this research are grade 1 teachers and grade 4 teachers at SDN 012 Labuhan Tangga Kecil. Data collection techniques use observation, interviews and documentation review. Data analysis uses the Miles and Huberman model. The results of the research show that the teachers at SDN 012 Labuhan Tangga Kecil have demonstrated quite good readiness and understanding regarding the implementation of the Independent Learning Curriculum. They have an awareness of the importance of effective learning planning and have demonstrated a commitment to designing learning experiences that are varied and focused on student understanding. Even though they experience challenges such as limited infrastructure and technology, they try to overcome these obstacles with creativity and collaboration. Their critical, reflective and open attitude shows readiness in the spirit of learning and continuous improvement in delivering more effective learning. The teachers also showed openness to exploring different learning methods, including the use of Teaching Modules (MA).